A Summary of the Research on the Effect of Gear Tooth Root Strengthening on Bending Fatigue Strength based on Residual Stress - Wang Zhen; Chen Long; Zheng Nan; Meng Xiangzhi; Yu Luosheng (Jixie chuandong)
With the continuous development of engineering technology, bending fatiguestrength has become an important limiting factor for the further development of gears, and bending fatigue failure is more dangerous than tooth surface failure. Based on the mechanism of gear bending fatigue fracture and the process of crack propagation, the influence factors of tooth root crack initiation, including tooth root transition fillet, grinding step and residual stress field, on tooth root bending fatigue properties are described. Based on the residual stress and the controllable tooth surface strengthening mechanism of surface and subsurface structure, the surface strengthening technology to improve the bending fatigue performance of gear is further analyzed, including shot peening strengthening, tooth root grinding technology and their research progress. The influence of root grinding on the bending fatigue performance of gears is discussed. It provides theoretical basis and technical reference for optimizing gear design and manufacturing and improving gear bending fatigue performance in engineering practice.